THE LOOM OF PENELOPE - Bortesi Longhi, Luis (2010)
Economic policy consists of direct and indirect measures taken by the government to ensure the general welfare of the nation. Direct measures are mandatory and hints are persuasive or dissuasive, but in all cases, are targeted to achieve economic and social development. However, we must highlight the issue of time limits, since some rules or orders are cyclical in nature but others, the most significant ones, must be stable and structural, that is what is known as the “state policies” that are based on a stable national compromise looming generational goals met in the medium and long term. If a model is constantly changing and periodic administration of every government clears the lateness in the previous final result is a resounding zero to the detriment of the country. That mentality is equivalent to that of Penelope, which to postpone their wedding date waiting for Odysseus, his consort, undid every night what wove during the day.